2006
DOI: 10.1016/j.ab.2006.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Single DNA molecule stretching measures the activity of chemicals that target the HIV-1 nucleocapsid protein

Abstract: We develop a biophysical method for investigating chemical compounds that target the nucleic acid chaperone activity of HIV-1 nucleocapsid protein (NCp7). We used an optical tweezers instrument to stretch single λ-DNA molecules through the helix-to-coil transition in the presence of NCp7 and various chemical compounds. The change in the helix-coil transition width induced by wild-type NCp7 and its zinc finger variants correlates with in vitro nucleic acid chaperone activity measurements and in vivo assays. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 39 publications
(67 reference statements)
0
32
0
Order By: Relevance
“…150,151 A recent study has also suggested that the dramatic effect of HIV-1 NC on DNA stretching may be used successfully as a test of possible drugs that may target NC and prevent HIV-1 replication. 152 …”
Section: Figure 11mentioning
confidence: 99%
“…150,151 A recent study has also suggested that the dramatic effect of HIV-1 NC on DNA stretching may be used successfully as a test of possible drugs that may target NC and prevent HIV-1 replication. 152 …”
Section: Figure 11mentioning
confidence: 99%
“…1). [51][52][53] However, NC-mediated fraying of the NA structure depends on the overall stability of the NA and requires natural mismatches as for wild-type TAR in order to take place. 46,54,57 This NC-mediated fraying of the NA structure largely relies on the hydrophobic plateau of the ZnF domain.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…This causes the transient opening of the 5' and 3' end sequences (short arrows), in a process called fraying and strand stretching (Single DNA molecule stretching measures the activity of chemicals that target the Hiv-1 nucleocapsid protein). 53 Binding of NC to TAr and cTAr causes the formation of nucleoprotein complexes where the nucleic acids are entirely coated by NC molecules. This causes the rapid hybridization of the complementary sequences resulting in the formation of a rNA:DNA hybrid within the nucleoprotein complex.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Studies have shown that all these three steps need the participation of NC proteins, especially the minus stand transfer step. 66,[78][79][80] The effect of NC's chaperone activity on these processes is detailed in the review by Levin and Musier-Forsyth in this special issue.…”
Section: Na Chaperone Proteins: Retroviral Nc Proteinsmentioning
confidence: 99%
“…It can also be used for testing drugs that may interfere with the chaperone activity of NC. 78 This can be more informative than other NC is needed for this activity, and that the gRNA within the aggregate is fully accessible to RT, even if RT was added after the RNA aggregation had occurred. All of these features illustrate the major role for reverse transcription of the NA aggregating ability of HIV-1 NC, together with the high mobility of RNA within these dense aggregates.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%